Peningkatan Hasil Belajar Matematika Tentang Operasi Hitung Bilangan Bulat Menggunakan Pita Bilangan - Tukino, Tukino (Pendidikan Matematika Universitas PGRI Yogyakarta, 2017)
This research aims to obtain information about the use of props model of bands of numbers in improving mathematics learning outcomes about the operation of arithmetic numbers in class V students I SD Negeri 4 Giriwoyo academic year 2017/2018.This research was conducted at SD Negeri 4 Giriwoyo UPT Education District Giriwoyo Wonogiri Regency, September to October 2017. The research method used is classroom action research with two learning improvement cycles. The object of this research is the students of grade V of SD Negeri 4 Giriwoyo, amounting to 14 students with details of 9 male students and five female students. Instruments for collecting data are student observation sheets in the learning process, teacher observation sheets in the learning process, and test of learning outcomes.The result of the research shows that there is an increase in learning result from initial condition 60,35 to 77,50 in cycle II (final condition). In addition, the number of students who reached the minimum criteria of completeness was increased from 3 students at the initial condition of 12 students on the final conditions. From the results of the above research can be stated that the use of model props can improve the results of mathematics learning about integer counting operations in Grade V students of first semester SD Negeri 4 Giriwoyo.Keywords: Operation Count, Number Band